“Wagner Festival Ravello” as a Sociocultural Phenomenon of the Festival Process in Italy: ДО 140-РІЧЧЯ ПРИБУТТЯ РІХАРДА ВАГНЕРА В РАВЕЛЛО - Ponomarenko, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the issue is due to the need to consider Italian music festivals as a component of national culture, to summarize their experience, which is important for musical life in general and for Ukraine in particular. The purpose of the article is to identify the prerequisites for the origin, the development process, as well as the modern vector of functioning of one of the most authoritative festivals in the south of Italy “Wagner Festival Ravello”, the 68th season of which took place in 2020. The scientific novelty lies in the fact that for the first time in Ukrainian art history, Italian music festivals are considered as an organic, artistic and economic component of the national culture, their traditional and innovative features are noted, and prospects for further development in the musical life of modern Italy. A detailed analysis of the Wagner Festival in Ravello will contribute to the dissemination of Italian experience for the organization and conduct of musical projects in Ukraine. The research methodology is based on the use of the inductive method, which, to characterize the festival process in the cultural life of Italy, involves the study of individual festival projects and provides for the use of a set of complementary research methods — historical-analytical, empirical and sociocultural. The historical-analytical method contributed to the understanding of the logic of the formation and development of the festival, the appeal to empirical and sociocultural methods made it possible to consider the features of the organization of the festival in the context of social relations in the system of musical life in modern Italy. Main results and conclusions. “Wagner Festival Ravello” is developing and constantly improving its capabilities. The high professional level of the international festival has been maintained for many years, and this is done thanks to the coordinated management of everyone involved in the organizational process. It should be noted that there is significant support from public authorities, as well as investments from the business sector. Within the framework of a modern project, there are creative scenes created using innovative technologies, orchestra of the Teatro San Carlo, the recording studio, the festival magazine — all these components of systemic activity are interconnected and aimed at ensuring an impeccable result. The Ravello Foundation has been leading and constantly developing the project for almost 20 years in order to represent the city of Ravello internationally as one of the cultural centers of the Campania region. Further creative life and the success of the festival require cooperation of cultural, financial, state institutions, constant technological renewal — everything that will allow the world to demonstrate the historical and artistic monuments of the City of Music and preserve the Wagner Festival of Ravello for future generations as an Italian cultural brand. Prospects for further research in this direction are: first, in a thorough study of the specifics of the functioning of music festivals in modern Italy and coverage of various aspects of the organization of this process; secondly, in the analysis of cooperation between the cultural, financial, tourism sectors, which affects the high level of organization and long-term creative life of festival events; thirdly, in considering the control system by the state, which should always be focused on professional support and represent the most important component of the functioning of art projects. All of the above will help domestic musicians learn about the specifics of organizing music festivals in Italy, as well as adopt and use it in the practice of musical life in modern Ukraine